IMPLEMENTASI AUGMENTED REALITY (AR) SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENGENALKAN FLORA DAN FAUNA LAHAN BASAH KEPADA SISWA SEKOLAH DASAR - Intan Diya Pitaloka; Aulia Widi Astuti; Nazella Putri Fadila; Shaffira Rahmiati4; Ahmad Suriansyah; Maimunah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The limited availability of learning media that can provide realistic visualization has hindered the introduction of wetland flora and fauna to elementary school students. Learning activities still rely on static two-dimensional images, making it difficult for students to comprehend the full characteristics of each organism. This paper aims to examine the potential of Augmented Reality (AR) as an interactive medium to enhance students’ understanding, learning motivation, and exploratory experiences related to wetland biodiversity. The study employs a qualitative approach using a Systematic Literature Review (SLR) based on relevant academic sources published between 2015 and 2025. The findings reveal that AR is capable of presenting realistic three-dimensional visuals, offering flexible exploration, and increasing students’ learning engagement. Improvements in students’ ability to identify organism characteristics, understand ecological relationships, and participate actively in observation activities were also documented. These results highlight AR’s strong potential as an immersive and effective learning tool that supports students in gaining a more comprehensive understanding of wetland ecosystems. Adequate technological support and teacher readiness remain essential for ensuring successful implementation of AR in elementary science education.